2018
DOI: 10.1186/s40425-018-0378-y
|View full text |Cite
|
Sign up to set email alerts
|

Salvage pembrolizumab added to kinase inhibitor therapy for the treatment of anaplastic thyroid carcinoma

Abstract: BackgroundAnaplastic thyroid carcinoma (ATC) is a rare but deadly form of thyroid cancer. Kinase inhibitors kinase inhibitors have shown clinical efficacy in the management of ATC, however, eventually these tumors acquire resistance to KI and patients succumb to their disease. Salvage therapy in this setting is limited. As ATC tumors diffusely express the programmed cell death protein ligand (PD-L1), anti- programmed cell death protein (PD-1) drugs such as pembrolizumab offer therapeutic potential. We sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
152
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 189 publications
(159 citation statements)
references
References 34 publications
4
152
0
3
Order By: Relevance
“…Therefore, there is a need for new treatment modalities, including targeted therapies and/or immunotherapies, mostly for patients who have advanced and/or poorly differentiated/undifferentiated cancers. More treatment options are available since the approval of kinase inhibitors; however, despite being effective, the duration of response to kinase inhibitors is limited, and disease ultimately progresses . To date, fine‐needle aspiration (FNA) cytology (FNAC) represents the main diagnostic tool for the evaluation of thyroid nodules.…”
Section: Pd‐l1 Expression and Thyroid Cancer Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, there is a need for new treatment modalities, including targeted therapies and/or immunotherapies, mostly for patients who have advanced and/or poorly differentiated/undifferentiated cancers. More treatment options are available since the approval of kinase inhibitors; however, despite being effective, the duration of response to kinase inhibitors is limited, and disease ultimately progresses . To date, fine‐needle aspiration (FNA) cytology (FNAC) represents the main diagnostic tool for the evaluation of thyroid nodules.…”
Section: Pd‐l1 Expression and Thyroid Cancer Diagnosismentioning
confidence: 99%
“…In a retrospective study from The University of Texas MD Anderson Cancer Center, 12 patients with ATC received pembrolizumab in combination with kinase inhibitors at the time of disease progression. Of these patients, 5 had a partial response, 4 had stable disease, and 3 had progressive disease . A recent phase 1b study of pembrolizumab monotherapy in 22 patients with PD‐L1–positive, advanced differentiated thyroid cancer showed that only 2 patients had confirmed partial responses lasting 8 and 20 months, respectively .…”
Section: Pd‐l1 Expression and Thyroid Cancer Diagnosismentioning
confidence: 99%
See 3 more Smart Citations